Flipped Classroom Learning among Medical and Dental Faculty of Bahria University Medical and Dental College - Dr. Shafaq Sultana; Prof. Dr. Talea Hoor; Dr. Madiha Ata (ziauddin University, 2024)
Background: Flipped classroom technique (FCR) is a pedagogical approach where students watch pre-recorded video lectures or read educational materials before coming to class. During class time, students then engage in activities, discussions, and problem-solving exercises related to the pre-recorded content, with the teacher acting as a facilitator and guide. The key to the effective utilization of this instructional method is that both the teachers and the students understand its educational philosophy and technique. This study aims at exploring the faculty's understanding and perceptions regarding flipping the classroom. Method: A Cross-sectional Descriptive study was carried out at Bahria university medical and dental college (BUMDC), Karachi, Pakistan from January to June 2020, after approval from the institutional ethical review committee. Data was collected through a self-designed questionnaire after obtaining verbal consent from 197 faculty members through non-probability purposive sampling. Data was analyzed by version 23.0 of Statistical Package for Social Sciences (SPSS). Results: The results revealed that more than half of the studied participants had a moderate perception regarding Flipped Classroom and more than one-third of those who were female, had a highly positive perception. According to designation and teaching experience, mean scores were higher for senior faculty as compared to junior faculty (p=0.02).   Conclusions: Contrary to popular belief, senior faculty also perceives this new technique as being beneficial for their teaching.  This opportunity should be utilized to train the faculty in conducting flipped classrooms in order to optimize its benefits.